2020
DOI: 10.3390/ma13051141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Covalent Functionalization of Carbon Nano-Onions with Pyrene Moieties for Supercapacitor Applications

Abstract: Herein, we report the surface functionalization of carbon nano-onions (CNOs) through an amidation reaction that occurs between the oxidized CNOs and 4-(pyren-4-yl)butanehydrazide. Raman and Fourier transform infrared spectroscopy methods were used to confirm the covalent functionalization. The percentage or number of groups in the outer shell was estimated with thermal gravimetric analysis. Finally, the potential applications of the functionalized CNOs as electrode materials in supercapacitors were evaluated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 73 publications
(81 reference statements)
0
8
0
Order By: Relevance
“…The CNO-Pyr electrodes exhibited 99% retention from its initial value after 1000 cycles. 140 The functionalization of carbon materials through an amidation reaction is stable under electrochemical conditions. The reason for the high stability of amide bonds is also discussed in section 3.1 (Table 5).…”
Section: Small Redox-active Molecules Functionalized On Other Cbms For Scsmentioning
confidence: 99%
“…The CNO-Pyr electrodes exhibited 99% retention from its initial value after 1000 cycles. 140 The functionalization of carbon materials through an amidation reaction is stable under electrochemical conditions. The reason for the high stability of amide bonds is also discussed in section 3.1 (Table 5).…”
Section: Small Redox-active Molecules Functionalized On Other Cbms For Scsmentioning
confidence: 99%
“…It is also observed that the vertical line in the low-frequency region of a-OLCs approaches 90° in comparison to the s-OLCs. This sharp increase at low frequency clearly indicates the enhanced capacitive behavior of a-OLCs [49] .…”
Section: Resultsmentioning
confidence: 86%
“…Additionally, a peak in the hydrogen underpotential deposition region is also seen. During the potential cycles, the cyclic voltammetry curves flatten progressively, and after 10 000 cycles only capacitive current can be observed, which can be attributed to the carbon support . This is indicative of a loss of active catalyst during the potential cycles, which could be caused by the common degradation mechanisms of fuel cell catalysts (particle dissolution, agglomeration, Ostwald ripening, and particle detachment from the carbon support).…”
Section: Resultsmentioning
confidence: 97%